Brine Infiltration in the Middle to Lower Crust in a Collision Zone: Mass Transfer and Microtexture Development Through Wet Grain–Boundary Diffusion. (19th December 2018) - Higashino, Fumiko; Kawakami, Tetsuo; Tsuchiya, Noriyoshi; Satish-Kumar, M; Ishikawa, Masahiro; Grantham, Geoffrey; Sakata, Shuhei; Hirata, Takafumi
Abstract: Brine-induced microtexture formation in upper amphibolite to granulite facies lower crust is investigated using a garnet–hornblende (Grt-Hbl) selvage developed along a planar crack discordantly cutting the gneissic structure of an orthopyroxene-bearing gneiss (central Sør Rondane Mountains, East Antarctica). The Cl contents of hornblende and biotite, K contents of hornblende and the thickness of relatively Na-rich rims of plagioclase decrease with distance from the center of the Grt–Hbl selvage (inferred position of the crack). Biotite and hornblende arrangement defining the gneissic structure can be traced into the selvage, suggesting that the wall-rock was overprinted by the selvage formation. Addition and loss of elements to the wall-rock was examined using Zr as an immobile element. Trace elements that tend to be mobile in brines rather than in melts are added to the wall-rock, indicating that the Grt–Hbl selvage was formed by the advection of NaCl–KCl brine into a thin crack. Plagioclase in the wall-rock shows a discontinuous drop of anorthite content at the rim, indicating that coupled dissolution–reprecipitation took place and the grain boundaries were once wet. Trace element concentrations in the wall-rock minerals decrease with distance from the crack, and, in most cases show exponentially decreasing/increasing profiles depending on the elements. These profiles are best modelled by a diffusion equation, suggesting that the wet grain–boundary diffusion in the wall-rock minerals controlled the observed mass transfer and resulted in dissolution–reprecipitation of mineral rims.